The Effect of Profitability and Inventory Intensity on Tax Avoidance - Abi Suryono; Marsuking; Setiorini, Kusumaningdiah Retno; Nila Hidayah (Journal of Economics and Social Sciences (JESS), 2025)
This study aims to analyze the effect of Profitability, and Inventory Intensity on Tax Avoidance in Food and Beverage Manufacturing Companies. This study is a quantitative study using secondary data, namely the financial statements of companies in the Food and Beverage Manufacturing Companies listed on the Indonesia Stock Exchange for the period 2020-2023. The sample in this study amounted to 29 companies with a purposive sampling technique. The data analysis method uses multiple linear regression. Analysis of the research results using SPSS 25. The results of the study indicate that simultaneously profitability and inventory intensity have an effect on tax avoidance. The results of the study indicate that partially profitability have an effect on tax avoidance, while inventory intensity have no effect on tax avoidance.